Estimasi nilai heritabilitas, ripitabilitas, korelasi genetik produksi susu dan kadar lemak Sapi Perah Fries Holland pada laktasi pertama dan kedua di Balai Besar Pembibitan Ternak Unggul – Hijauan Pakan Ternak Baturraden - Nani S Kubangun; Since Lumatauw; Budi Santoso (Program Pascasarjana Universitas Papua, 2018)
This study aims to determine the value of heritability, ripitability, genetic correlation and fat level of dairy cows in the first and second lactation. The results showed that the heritability value obtained was categorized high. The heritability value of daily milk production in the first lactation was 0.402 ± 0.259 and in the second lactation was 0.54 ± 0.301. Heritability value of fat content obtained is high that is 0.63 ± 0.39. The average value of milk production ripitability and the value of ripitability of fat level including high value category that is equal to 0.49 ± 0.325 and 0.93 ± 0.13. The genetic correlation value of milk production and fat level obtained in this study was 2.91 ± 0.83.